Respuesta :

Answer:

Option D is the correct answer

Step-by-step explanation:

[tex](3 {m}^{ - 4} )^{3} (3 {m}^{5} ) \\ \\ = {3}^{3} {m}^{ - 4 \times 3} \times 3 {m}^{5} \\ \\ = 27 \times 3 \times {m}^{ - 12 + 5} \\ \\ = 81 {m}^{ - 7} \\ \\ = \frac{81}{ {m}^{7} } [/tex]

Answer:

the correct answer is D

Step-by-step explanation:

distribute the exponent on the left to get the expression ((3^3)(m^-12))(3(m^5))

bring the negative exponent to the denominator to get (3^4)(m^5)/(m^12)

subtract the exponents of m to get an answer of 81/(m^7)

ACCESS MORE